ROBUST CONTROL FOR PRECISION MOTION OF A THIN AND COMPACT LINEAR SWITCHED RELUCTANCE MOTOR - Maslan, M.N.; Sato, K. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
This study presents the robustness of the precision motion control system of a thin and compact linear switch reluctance motor (LSRM). The control system employs a linearizer unit along with a feed forward element and a disturbance observer for precision motion performance. Although numerous tracking experiments were carried out to evaluate the effectiveness, their robustness towards sudden load and speed change remains unclear. We performed a sudden load of 50% change in mass and a sudden speed variation 4 times as fast as initially. By conducting the experiments, we found that it takes approximately 0.05 s for the control system to regulate to the determined ramp-reference motion, and the precision motion performance was maintained having a maximum absolute tracking error of less than 5 μm. In conclusion, these results indicate that the control system has the ability to quickly suppress the sudden load and speed change.